2018
DOI: 10.1002/2017jb014983
|View full text |Cite
|
Sign up to set email alerts
|

Locations of Injection‐Induced Earthquakes in Oklahoma Controlled by Crustal Structures

Abstract: In recent years, many small‐ to moderate‐size earthquakes occurred in central northern Oklahoma, likely associated with wastewater injection. The most recent one is the M5.8 Pawnee earthquake occurred on 3 September 2016. It is still not clear what controls the locations of these injection‐induced earthquakes. Here we conduct 2‐D Pg wave tomography with anisotropy to image seismogenic structures in this region, using more than 10 years of Pg arrivals recorded by 81 seismic stations. Our high‐resolution Pg wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…The absence of triggered aftershocks on the deeper part of the fault and the depth‐distribution of regional seismicity suggest that the deeper fault may be stronger and further from critically stressed than shallower parts of the fault. Variations in fault strength may be explained by several mechanisms: (1) stress concentrations or reduced normal stresses due to coseismic effects, structural discontinuities, or initial/redistributed pore fluids (e.g., Manga et al, ; Nur & Booker, ; Pei et al, ; Pollitz et al, ); (2) aseismic response of parts of the fault (e.g., Barnhart et al, ; Chen et al, ; Guglielmi et al, ); or (3) that the deeper part of the fault is stronger than the shallower part of the fault, thereby inhibiting aftershock triggering and limiting the depth of seismicity, regionally. A reduction in the pore pressure changes with depth is one mechanism by which the shallower parts of the fault may be weakened relative to the deeper parts of the fault, and this mechanism may also explain the aftershock distribution and features of the earthquake rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of triggered aftershocks on the deeper part of the fault and the depth‐distribution of regional seismicity suggest that the deeper fault may be stronger and further from critically stressed than shallower parts of the fault. Variations in fault strength may be explained by several mechanisms: (1) stress concentrations or reduced normal stresses due to coseismic effects, structural discontinuities, or initial/redistributed pore fluids (e.g., Manga et al, ; Nur & Booker, ; Pei et al, ; Pollitz et al, ); (2) aseismic response of parts of the fault (e.g., Barnhart et al, ; Chen et al, ; Guglielmi et al, ); or (3) that the deeper part of the fault is stronger than the shallower part of the fault, thereby inhibiting aftershock triggering and limiting the depth of seismicity, regionally. A reduction in the pore pressure changes with depth is one mechanism by which the shallower parts of the fault may be weakened relative to the deeper parts of the fault, and this mechanism may also explain the aftershock distribution and features of the earthquake rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the Fairview sequence, which is likely related to the high‐rate injection wells to the northeast (Goebel et al, ; Yeck et al, ), which does exhibit unilateral migration toward the southwest before aftershocks were removed, and the current activities (as of 2017) are concentrated to the southern end of the fault. Pei et al () suggest that the locations of large (e.g., M 4.5+) earthquakes are likely controlled by large‐scale geological structure. The individual cluster diffusivities are consistent with the ranges of diffusivities from other crustal earthquake sequences and induced seismicity (e.g., Chen et al, ; Shapiro et al, ; Talwani et al, ), suggesting common properties for fluid‐triggered seismicity in the crust. Only 40% to 50% of the clusters exhibit statistically significant diffusive migration behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous works have also shown that the characteristics of induced seismicity depend not only on the injected volume, but also on the reservoir geological structure 17 , 31 , 32 , the depth of injection and the stress state 33 – 35 , the density and frictional properties of faults 26 , 36 and the hydraulic properties of the reservoir/fault system 37 , 38 . Therefore, understanding induced seismicity only based on the measurement of the injected fluid volume can be problematic.…”
Section: Introductionmentioning
confidence: 99%